Lip Synchrony of Rounded and Protruded Vowels and Diphthongs in the Lithuanian-Dubbed Animated Film “Cloudy with a Chance of Meatballs 2” - Koverienė, Indrė; Čeidaitė, Kristina (Respectus Philologicus, 2020)
In this article, the problems of dubbing, especially related to lip synchrony as one of the most challenging aspects of audiovisual translation, are scrutinised. Contrarily to the traditional focus on bilabials and open vowels, the object of this research is lip synchrony of both rounded and protruded vowels and diphthongs since lip rounding is a visibly marked feature, which cannot be neglected especially in close-ups. The study aims at determining the inaccuracies in lip synchrony of the mentioned phonemic group in the dubbed animated feature film Cloudy with a Chance of Meatballs 2 from English to Lithuanian. Qualitative and quantitative analysis is carried out by employing a comparative method. The research methodology is based on the theoretical insights and assumptions provided by Frederic Chaume (2004, 2006, 2012), Richard Barsam & Dave Monahan (2010), and Indrė Koverienė (2015). The research findings demonstrate the main issues of lip synchrony a translator might face while adapting a piece of audiovisual material for the target language audience. Also, it provides insights into the quality of the overall translation of the chosen film.
Keywords: dubbing; lip synchrony; viseme; vowels; diphthongs